THE ROLE OF BAMUIS BNI ORGANIZATIONAL COMMUNICATION TOWARDS YOUNG PREACHER'S PRODUCTIVITY IN UNIVERSITAS IBN KHALDUN BOGOR - Hikmah Ismidiana Shafa; Dewi Anggrayni; Suyud Arif, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The development of digital media has reshaped Islamic preaching (da’wah), shifting its space from traditional forums to dynamic online platforms. However, this transition also reveals a critical gap: the lack of effective communication strategies among young preachers in addressing diverse audiences and combating misinformation. This study explores how BAMUIS BNI’s organizational communication supports the productivity of young da’i at Universitas Ibn Khaldun Bogor by examining internal communication processes, motivation systems, and evaluative feedback mechanisms. The findings aim to address the broader issue of ineffective message delivery in contemporary Islamic outreach. The study employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. The results highlight both the achievements and areas for development in BAMUIS BNI’s organizational communication strategy, with implications for enhancing da’wah quality and sustainability.